Development and preliminary evaluation of a group intervention targeting maternal mental health and mother–infant interactions: a combined qualitative and case series report. (27th May 2018) - Coo, Soledad; Somerville, Susanne; Matacz, Rochelle; Byrne, Shannon
Abstract: Objective and Background: The purpose of this study was to investigate the outcomes of an Emotional Wellbeing Group intervention developed to treat maternal depression and anxiety while concurrently supporting positive development of the mother–infant relationship. Method: Five women diagnosed with depressive and/or anxiety disorders and their infants completed the Emotional Wellbeing Group. The participants completed pre- and post- intervention assessments which included self-report measures of mood and the motherhood experience, and a video-taped, unstructured play session between mothers and their infants. Results: Four of the participants reported a clinically significant decrease in their symptoms of anxiety. All mothers reported more positive perceptions of their infants and their experience of motherhood, and showed enhanced maternal sensitivity and responsiveness towards their infants. Depression levels were not shown to improve consistently. Conclusion: This study provides initial positive evidence to support future research directions and clinical efforts to develop interventions that target both the treatment of perinatal depression and anxiety and the quality of mother–infant interactions. Clinical insights for mental health professionals working with mothers and infants are presented.